An Analysis of the Collective Effectiveness of the Romanian National Team's Attacks during 2019 World Women's Handball Championship - GHEORGHE C.; Mereuță C. (Editura Universitatii Transilvania din Brasov, 2020)
The aim of this study is to analyse (i) the collective effectiveness in the attack phases of team Romania at the Women World Championship in Japan, 2019 and (ii) whether the forced changes made just two days before the start of the competition had any impact on the final results. As it had been through a generational transition and had also been confronted with injuries and doping cases right before the debut of the competition, the Romanian team had an unstable evolution, being either severely defeated or winning games by a low margin. Game expertise and scoring index were the main factors that affected the ranking, to the disadvantage of Romania, in this important tournament.